EVALUASI KEBIJAKAN PENYELENGGARAAN PENDIDIKAN INKLUSIF TINGKAT SEKOLAH DASAR DI KECAMATAN KOJA JAKARTA UTARA (Studi Pada SDN Tugu Utara 11) - Azizah Febrianti Fasha; Nina Widowati (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2017)
In Indonesia, everyone has the right to education including children with disabilities. Indonesian Government established a regulation related to this matter which is Inclusive Education Policy. Inclusive Education is an education system that gives everyone access to education including children with special needs. Inclusive Education Policy is also applied in the capital city of Indonesia, the Special Capital Region of Jakarta. In Jakarta, inclusive education is regulated through governor regulation which is Governor Regulation Number 116 of 2007 on The Implementasion of Inclusive Education. In its implementation, there are still some problems therefore the evaluation about this policy is needed. This paper describes the evaluation of inclusive education policy at one of public primary schools in Jakarta which is Tugu Utara 11 Public Primary School. Data collection techniques of this research were observation, interview, and literature review. Collected data were analyzed by qualitative descriptive method. This research used the theory from William N. Dunn, Criteria for Evaluating Policy Performance which are Effectiveness, Efficiency, Adequacy, Equity, and Responsiveness as the main theory.Based on the evaluation, the implementation of inclusive education on the research site is still not optimal. The paper concludes with a consideration of possible acts for improvements in the implementation of inclusive education that need to be kept in mind.